Avaliação da qualidade da água superficial do canal São Joaquim, Belém - PA - PAREDES, Brenda Melise Morbach (Universidade Federal do Pará, 2017)
The process of urbanization and illegal occupation of urban channel margins nearby areas generate large impacts on these water bodies, the main one being the discharge of effluents. The channel São Joaquim, Belém Pa, is considered the largest urban channel Bethlehem, and already suffers from such impacts, as well as being affected by the lack of sanitation in its Sub Basin, such a situation can be observed in the results obtained in 12 months sampling over three points from its source to its mouth. This study aimed to analyze the said water quality Canal in physical, chemical and biological parameters through the IQA and application of descriptive statistics, analytical and multivariate analysis, being possible to observe the degradation of this water body caused mainly by organic matter, which was obtained through the OD analysis, BOD, total nitrogen, total phosphorus, and thermotolerant coliforms. The Water Quality Index was calculated for the Channel and was obtained the value of 49 classifying it as quality "acceptable." When performing a seasonal comparison between dry periods and wet, and tide conditions, using the Mann Whitney hypothesis tests and test T Student, it was observed that there was significant variability between the variables, except for the temperature, which It showed a variation between the dry and rainy seasons. The analysis of variance (ANOVA) was applied for the verification of similarity between the points for each variable analisada.Ao perform a temporal assessment of water quality of the channel between the years 1988; 2002; 2005; 2006; 2011 and 2014, it was observed that the degradation of the channel has a history of nearly 30 years, a situation confirmed by the analysis of indicator variables of organic matter. The principal component analysis led to the formation of three components that together represented 67.53% of the variability of the data, and these variables explained by the ACP, anthropic action indicative.